Five principles to prioritise in small-scale surgical quality improvement: a qualitative study of the views of surgical improvement leaders - Mary Dixon-Woods; Graham Martin; Alessandra Giusti; Clifford Y Ko (BMJ Open Quality)
Objective Variations in the quality and safety of surgical care remain persistent. Efforts to improve are needed, but are themselves variably effective, with often disappointing impacts. When compared with large-scale, multisite and better resourced improvement efforts, the evidence base for small-scale quality improvement (QI) has remained under-developed and lacking in clarity on good practice. We aimed to identify experienced leaders’ views on the principles that should guide small-scale QI projects in surgery.Methods Two rounds of virtual focus groups were conducted with 10 QI leaders, comprising surgeons, anaesthetists and nurses from three countries (Ireland, the UK and the USA). All participants had formal training in improvement techniques and at least 10 years’ experience leading small-scale QI efforts in surgery. Analysis was informed by the principles of the constant comparative method together with content analysis.Results Analysis of the focus groups identified five principles to prioritise for small-scale surgical QI: ensure high-quality planning before project launch; understand the problem to be solved to define focused project aims; ensure improvement efforts are sensitive to time, capacity and local context; assemble the right improvement team and engage the relevant stakeholders; and use of a clear, structured framework to guide QI is likely to be very helpful.Conclusions This study identifies five principles likely to be useful in guiding better surgical QI in frontline settings. These principles can help inform a structured framework to support small-scale surgical improvement efforts.